GUS DUR’S IDEAS IN INFLUENCING POSTCOLONIAL ISLAMIC NUSANTARA THOUGHT - Subekti, Fiqi Restu; Mutiullah (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The present article examines the influence of the thought of KH. Abdurrahman Wahid (Gus Dur) on the formation of postcolonial discourse in the context of Islam Nusantara. In the postcolonial context, the Islamic construction of the Archipelago is inextricably linked to colonial epistemological legacies and the hegemony of external cultures, particularly Arabic. Gus Dur’s thought process can be understood as a deconstructive effort against the dichotomy between “pure” and “local” Islam that was created by colonial powers and puritan movements. It is evident that Gus Dur’s rejection of the uniformity of Arab culture as the sole representation of Islam was underpinned by a sharp critique of arabisation. As an alternative, he proffered the concept of Islamic pribumisation, defined as the adjustment of Islamic expression to local cultural values without sacrificing the substance of the teachings. Furthermore, Gus Dur placed significant emphasis on the necessity of contextualising Islamic teachings, emphasising the importance of re-evaluating Islamic values in accordance with the prevailing social and cultural dynamics of Indonesian society. It is asserted that an approach of this nature will engender the concepts of pluralism and tolerance, which will in turn serve as the primary foundations upon which religious life is to be constructed. The present study employs a qualitative approach, utilising critical discourse analysis of Gus Dur’s ideas and relevant supporting literature. The findings demonstrate that Gus Dur’s thought plays a significant role in formulating the paradigm of Islam Nusantara. This paradigm is characterised by its responsiveness to local realities, its transcendence of religious formalism, and its rehabilitation of cultural dignity as an integral part of Islamic expression. Consequently, the thought of Gus Dur constitutes a significant contribution to the development of a plural, humanist and contextual Islamic civilisation.